Swedish Plectida (Nematoda). Part 2. The genus Antomicron Cobb, 1920 - Holovachov, Oleksandr (Zootaxa, 2012)
Two new species of Antomicron are described from bottom sediments collected in Gullmarn Fjord, west coast of Sweden.A. quindecimpapillatus sp. n. is particularly characterised by the 1390–1459 µm long body; elongate doughnut-shapedamphid; straight vagina with drop-shaped sclerotizations; female without sensilla in pharyngeal region and without sup-plements; male with two pairs of setiform sensilla in pharyngeal region, 15 tubular and no alveolar supplements, one pairof precloacal and four pairs of caudal setae, 26.0–29.5 µm long spicules. A. lorenzeni sp. n. is particularly characterisedby the 603–676 µm long body; an inverted U-shaped amphid; straight vagina without sclerotizations; female without sen-silla in pharyngeal region and without supplements; male without sensilla in pharyngeal region, two tubular and nine al-veolar supplements, one pair of precloacal and four pairs of caudal setae, 23 µm long spicules. Additional information onthe males of Antomicron pellucidum, A. elegans, A. pratense and A. intermedius is provided. A taxonomic review, tabular compendium and identification key of species of the genus Antomicron are also given.